2016
DOI: 10.1177/1076029616646874
|View full text |Cite
|
Sign up to set email alerts
|

CHA2DS2-VASc Score Predicts In-Hospital and Long-Term Clinical Outcomes in Patients With ST-Segment Elevation Myocardial Infarction Who Were Undergoing Primary Percutaneous Coronary Intervention

Abstract: CHADS-VASc score includes similar risk factors for coronary artery disease. We hypothesized that admission CHADS-VASc score might be predictive of adverse clinical outcomes for patients with ST-segment elevation myocardial infarction (STEMI) who were undergoing primary percutaneous coronary intervention. A total of 647 patients with STEMI enrolled in this study. The study population was divided into 2 groups according to their admission CHADS-VASc score. The low group (n = 521) was defined as CHADS-VASc score … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 23 publications
3
32
1
2
Order By: Relevance
“…The proportion of patients with post-procedural TIMI grade < 3 was higher in the high-risk group compared to the other groups. The CHA 2 DS 2 -VASc score was shown to indicate the severity of coronary artery disease in previous studies [3]. Our results support these previous studies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The proportion of patients with post-procedural TIMI grade < 3 was higher in the high-risk group compared to the other groups. The CHA 2 DS 2 -VASc score was shown to indicate the severity of coronary artery disease in previous studies [3]. Our results support these previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…However, it was recognised to also be usefulin the prediction of the severity of coronary artery disease [2] and coronary artery disease-related mortality due to the presence of some common risk factors [3]. It may also be used for prediction of mortality and morbidity in congestive heart failure patients who are candidates for cardiac re-synchronisation treatment [4] and thrombotic events developing after percutaneous coronary intervention (PCI) [5].…”
Section: Introductionmentioning
confidence: 99%
“…This study revealed a dual prognostic utility of CHA2DS2-VASc for both suboptimal reperfusion and short-term mortality. This coincides with many studies who found a useful surrogate measure of in-hospital mortality independent of nore low [5,12,[14][15][16][17][18].…”
Section: Discussionsupporting
confidence: 89%
“…Bununla birlikte HT'nin, yine Mİ sonrası hastaların mortalitesini gösterdiği iyi bilinmektedir (39,40) . Yaş, DM, HT ve cinsiyet gibi STYMİ hastalarında mortaliteyi arttırdığı gösterilmiş faktörlerle birlikte EQ5D skorlarının çoklu Cox regresyon analizi ile değerlendi-rildiğinde indeks skorun mortalite artışını 5.5 kat daha fazla ön gördürdüğü çalışmamızda tespit edilmiştir (41) . EQ5D indeks skoru STYMİ hastalarında uzun dönemli mortalitenin bağım-sız bir ön gördürücüsü olarak değerlendirilmiştir.…”
Section: Discussionunclassified